The art of digital marketing : the definitive guide to creating strategic, targeted and measurable online campaigns - Dodson, Ian (John Wiley & Sons, Inc., 2016)
"The premier guide to digital marketing that works, and a solid framework for success The Digital Marketing Playbook is the comprehensive guide to cracking the digital marketing 'code, ' and reaching, engaging, and serving the empowered consumer. Based on the industry's leading certification from the Digital Marketing Institute (DMI), this book presents an innovative methodology for successful digital marketing: start with the customer and work backwards. A campaign is only effective as it is reflective of the consumer's wants, needs, preferences, and inclinations; the DMI framework provides structured, implementable, iterative direction for getting it right every time. The heart of the framework is a three-step process called the 3i Principles: Initiate, Iterate, and Integrate. This simple idea translates into higher engagement, real customer interaction, and multichannel campaigns that extend even into traditional marketing channels. The evolution of digital marketing isn't really about the brands; it's about consumers exercising more control over their choices. This book demonstrates how using this single realization as a starting point helps you build and implement more effective campaigns. Get inside the customer's head with deep consumer research Constantly improve your campaigns based on feedback and interactions Integrate digital activities across channels, including traditional marketing Build campaigns based on customer choice and control Digital marketing turns traditional marketing models on their heads. Instead of telling the customer what to think, you find out what they already think and go from there. Instead of front-loading resources, you continually adjust your approach based on real interactions with real customers every day. Digital marketing operates within its own paradigm, and The Digital Marketing Playbook opens the door for your next campaign"- Resumé vydavatele